Zapisz w postaci najprostrzej
a (5x-6)-(4x-7)
b -7y+(8+y)+3
c -9a-(4a-7)+8(7+a)
d (5a-ab)-4a(b+2)
e (x-2)(2x+4y)
f(5x-7)(4+2x)


Odpowiedź :

a) (5x - 6) - (4x - 7) = 20x² - 35x - 24x + 42 = 20x² - 11x + 42

b) - 7y + (8 + y) + 3 = - 7y + 8 + y + 3 = - 6y + 11

c) - 9a - (4a - 7) + 8(7 + a) = - 9a - 4a + 7 + 56 + 8a = - 5a + 63

d) (5a - ab) - 4a(b + 2) = 5a - ab - 4ab - 8a = - 3a - 5ab

e) (x - 2)(2x + 4y) = 2x² + 4xy - 4x - 8y  

f) (5x - 7)(4 + 2x) = 20x + 10x² - 28 - 14x = 6x + 10x² - 28

liczę na naj